Respuesta :
Answer:
A. [tex]f(x)=(x+6)(x+2)(x-3)[/tex]
Step-by-step explanation:
The zeros or roots of a function are the numbers that when they are entered into the function the output will be 0.
We will evaluate the given numbers (-6,-2,3)to see in wich option all of them wil give us 0 in the output, Let´s start with the first option A) as follows:
[tex]f(-6)=((-6)+6)((-6)+2)((-6)-3)=(0)(-4)(-9)=0[/tex]
[tex]f(-2)=((-2)+6)((-2)+2)((-2)-3)=(4)(0)(-5)=0[/tex]
[tex]f(3)=((3)+6)((3)+2)((3)-3)=(9)(5)(0)=0[/tex]
As we can see this is the correct option in which all of the values give us the output 0 adn we dont need to evaluate the resto of the options (B), C) and D))